Altered polarity and expression of H+-ATPase without ultrastructural changes in kidneys of Dent's disease patients. - Moulin, P; Igarashi, T; Van der Smissen, P; Cosyns, J; Verroust, P; Thakker, R; Scheinman, S; Courtoy, P; Devuyst, O (2003)
BACKGROUND: Dent's disease is a proximal tubule (PT) disorder characterized by low-molecular-weight proteinuria (LWMP) that may be associated with hypercalciuria, nephrocalcinosis, and renal failure. It is caused by inactivating mutations of the renal chloride channel ClC-5, which colocalizes with the vacuolar H+-ATPase in PT cells and alpha-type intercalated cells. Examinations of knockout mice have established the role of ClC-5 in PT endocytosis, but the consequences of ClC-5 mutations on the polarity of H+-ATPase and other plasma membrane proteins remain unknown. METHODS: We have studied renal biopsies from eight patients with Dent's disease, due to inactivating ClC-5 mutations, by light and electron microscopy, and by immunohistochemical staining. All patients exhibited LMWP, and renal function ranged from normal to end-stage renal failure. RESULTS: Light microscopy revealed either normal renal architecture or glomerulosclerosis, tubular dedifferentiation and atrophy, and mild interstitial fibrosis. Focal, hyaline casts, sometimes calcified, were identified at all stages. Electron microscopy did not reveal any ultrastructural abnormalities in PT cells, and the endocytic apparatus was apparently normal. However, immunohistochemical studies demonstrated a consistent inversion of H+-ATPase polarity in PT cells to a basolateral distribution contrasting with its apical location in the normal kidney. This inversion of polarity was specific for H+-ATPase and did not affect distribution of aminopeptidase, megalin, and Na+/K+-ATPase. Furthermore, apical H+-ATPase expression was absent in alpha-type intercalated cells. CONCLUSION: ClC-5 mutations are associated with modifications in the polarity and expression of H+-ATPase, but not ultrastructural alterations in PT cells. These findings help further understanding of the role of ClC-5 and the pathophysiology of Dent's disease.